2015
DOI: 10.11124/jbisrir-2015-2150
|View full text |Cite
|
Sign up to set email alerts
|

Exploring conceptual and theoretical frameworks for nurse practitioner education: a scoping review protocol

Abstract: The use of conceptual and theoretical frameworks to organize the educational curriculum of nursing programs is essential to protect and preserve the focus and clarity of nursing's distinct contribution to health care. Conceptual frameworks of nursing provide a means to look at nursing in relationship to external factors, thereby assigning meaning to the practice. Graduate level nursing education in the preparation of Nurse Practitioners (NPs) specifically and Advanced Practice Nurses (APNs) in general, is sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 13 publications
1
21
0
3
Order By: Relevance
“…On the contrary, low levels of self-efficacy have been considered a barrier to task performance and goal achievement (Boswell et al; 2020; Cope et al, 2020; Hernández-Padilla et al, 2016; Nuttall, 2018). Assessing nurses’ self-efficacy can contribute to highlight their educational needs and inform the development of new educational programs in nurse prescribing (Hall et al, 2020; Wilson et al, 2015). Nonetheless, to the best of our knowledge, there are no validated tools that allow for a valid and reliable assessment of self-efficacy in nurse prescribing.…”
Section: Nurse Prescribing and Self-efficacymentioning
confidence: 99%
“…On the contrary, low levels of self-efficacy have been considered a barrier to task performance and goal achievement (Boswell et al; 2020; Cope et al, 2020; Hernández-Padilla et al, 2016; Nuttall, 2018). Assessing nurses’ self-efficacy can contribute to highlight their educational needs and inform the development of new educational programs in nurse prescribing (Hall et al, 2020; Wilson et al, 2015). Nonetheless, to the best of our knowledge, there are no validated tools that allow for a valid and reliable assessment of self-efficacy in nurse prescribing.…”
Section: Nurse Prescribing and Self-efficacymentioning
confidence: 99%
“…Throughout this review, the following key terms are used as follows: African nurse was defined as a registered nurse who has graduated from an accredited and/or approved nursing programme, successfully passing the nurses registration examination and who has been working in any African country (Wilson et al, 2015). In this manner, we avoided including works where the care of people with mental health needs was applied by other participants such as the family, local leaders or other professionals.…”
Section: Samplingmentioning
confidence: 99%
“…Kermansaravi et al [32] found that students liked theoretical contents that had applied value; otherwise studying them was a waste of time. We can state that there was a preference for biomedical courses, which could contrast/contradict the long struggle of nursing to carry out the conceptual and theoretical framework change in nursing training, as opposed to the traditional biomedical model [35]. In any case, the credit load is revisable and susceptible to modification, since the number of credits that each course must be is not stipulated by any Spanish law [5,26,27].…”
Section: Discussionmentioning
confidence: 99%